Blood Pressure Measurement at Two Years in Offspring of Women Randomized to a Trial of Metformin for Gdm: Follow up Data From the MiG Trial - Battin, MR; Obolonkin, V; Rush, E; Hague, W; Coat, S; Rowan, J (BioMed Central, 2015)
Offspring born following maternal gestational diabetes are at risk of excessive childhood weight gain and Type 2 diabetes in childhood, which in turn is associated with an increased rate of hypertension. We aimed to determine the systolic and diastolic blood pressure at two years of age in a cohort of children exposed to gestational diabetes mellitus using data from the MiG trial of metformin use in gestational diabetes. The secondary aim was to analyze these data by randomization of treatment to insulin or metformin.
Keywords: Gestational diabetes; Metformin; Hypertension; Childhood blood pressure